PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK CERITA PADA SISWA KELAS III SDN 1 TATURA PALU - Krismawati, Ike (BAHASANTODEA, 2016)
Basen on the explanation on the background of rhis research, the formula of this reearch: how is the application of coopertive learning model  can improve  learning income in scrutinize of a story at the third grade students of SDN 1 Tatura Palu? and how is the improvement of cooperative learning model ability in learning  scrutinize of the story at the third grade students of SDN 1 Tatura Palu? the objective of this research to describe application of coopertive learning model  in scrutinize of story ability at the third grade students of SDN 1 Tatura Palu and to improve scrutinize of the story ability with using cooperative learning in the scrutinize of the story learning at the third grade students of SDN 1 Tatura Palu. Kind of this research is a classroom actio research which implemented by a cycl. Each of cycle of this research consist of 4 steps, there are 1) plannning step, 2) action, 3) observation, 4) reflection. Based on the result of this reserach, there are five aspects os assesment, those are backgorund aspect, plot aspect, person and personage, content and theme. Based on the assesment of background aspect of cycle I is 34,78% and cycle Ii is 91,30%. Person and personage aspect of cycle I is 47,82% and in the cycle II is 78,26%. Plot aspect at the cycle I is 26,08% and at the cycle II is 78,26%. Content aspect at the cycle I is 30,43% ad at the cycle II is 91,30%. Theme aspect at the cycle I is 34,78% and at the cycle II is 69,56%. At the cycle I the percentage of completeness achieve 21,73% an at the cycle II happen an improvement to be 82,60%. All of the aspects had an improvement from cycle I to cycle II. At the cycle I the average of percentage completeness is 61 and at the cycle II had an improvement and the average percentage of completenes tobe 85,39. It can state that the reseacrh which found with a title application of cooperative learning can improve scrutinize ability of the story at the third grade students of SDN 1 Tatura Palu.